Case-based learning: A ‘Case’ for restructuring anatomy education in Indian nursing curriculum - Das, Sebi; Ponnusamy, Kumarasamy Appu; Tripathi, Apoorva; Jaison, Judith; Rathinam, Bertha A. D. (Journal of Education and Health Promotion, 2022)
Teaching anatomy in a clinical context can aid students in appreciating how the subject will apply to their future career as nurses as well as in other administrative roles. Anatomy is voluminous, making it difficult to retain the factual information in the long run; therefore, this study primarily focuses on whether case-based learning (CBL) with integrated anatomy learning can help in retention of the information over short as well as long spans of time. It also focuses on how profitable would the students be with this different style of learning, and whether it can facilitate in better understanding of the basic and clinical concepts.BACKGROUNDTeaching anatomy in a clinical context can aid students in appreciating how the subject will apply to their future career as nurses as well as in other administrative roles. Anatomy is voluminous, making it difficult to retain the factual information in the long run; therefore, this study primarily focuses on whether case-based learning (CBL) with integrated anatomy learning can help in retention of the information over short as well as long spans of time. It also focuses on how profitable would the students be with this different style of learning, and whether it can facilitate in better understanding of the basic and clinical concepts.The current study was conducted in the Nursing College of All India Institute of Medical Sciences, Bhopal, India to integrate CBL and evaluate its effect compared to the highly compartmentalized, didactic lectures among the nursing students. The extent of knowledge retention was analyzed by conducting a series of tests before as well as after CBL intervention. Feedback and suggestions were obtained from the students by using the 5-point Likert scale method.MATERIALS AND METHODSThe current study was conducted in the Nursing College of All India Institute of Medical Sciences, Bhopal, India to integrate CBL and evaluate its effect compared to the highly compartmentalized, didactic lectures among the nursing students. The extent of knowledge retention was analyzed by conducting a series of tests before as well as after CBL intervention. Feedback and suggestions were obtained from the students by using the 5-point Likert scale method.The post-test scores of the students improved by 21% after the CBL. More than 85% of the students opined that CBL improves critical thinking, team work, self-directed learning, and communication skills.RESULTSThe post-test scores of the students improved by 21% after the CBL. More than 85% of the students opined that CBL improves critical thinking, team work, self-directed learning, and communication skills.CBL promotes effective short-term retention and facilitates comprehension of key concepts. CBL also plays an important role in improving the professional skills of the students, which otherwise is not taught, and equips them for their future careers.CONCLUSIONCBL promotes effective short-term retention and facilitates comprehension of key concepts. CBL also plays an important role in improving the professional skills of the students, which otherwise is not taught, and equips them for their future careers.